Enhanced bioactivity and osteoinductivity of carboxymethyl chitosan/nanohydroxyapatite/graphene oxide nanocomposites. Issue 32 (16th May 2018) - Yu, Zhang; Xiao, Caiwen; Huang, Yazhuo; Chen, Mingjiao; Wei, Wei; Yang, Xiaoxuan; Zhou, Huifang; Bi, Xiaoping; Lu, Linna; Ruan, Jing; Fan, Xianqun
Abstract : The CMC/nHA/GO scaffold with the surface chemistry and roughness dual effects and the release of phosphate and calcium ions synergistically assist the mineralization and facilitate the bone regeneration. Abstract : Tissue engineering approaches combine a bioscaffold with stem cells to provide biological substitutes that can repair bone defects and eventually improve tissue functions. The prospective bioscaffold should have good osteoinductivity. Surface chemical and roughness modifications are regarded as valuable strategies for developing bioscaffolds because of their positive effects on enhancing osteogenic differentiation. However, the synergistic combination of the two strategies is currently poorly studied. In this work, a nanoengineered scaffold with surface chemistry (oxygen-containing groups) and roughness ( R q = 74.1 nm) modifications was fabricated by doping nanohydroxyapatite (nHA), chemically crosslinked graphene oxide (GO) and carboxymethyl chitosan (CMC). The biocompatibility and osteoinductivity of the nanoengineered CMC/nHA/GO scaffold was evaluated in vitro and in vivo, and the osteogenic differentiation mechanism of the nanoengineered scaffold was preliminarily investigated. Our data demonstrated that the enhanced osteoinductivity of CMC/nHA/GO may profit from the surface chemistry and roughness, which benefit the β1 integrin interactions with the extracellular matrix and activate the FAK–ERK signaling pathway to upregulate the expression of osteogenic special proteins. This study indicates that the nanocomposite scaffold with surface chemistry and roughness modifications could serve as a novel and promising bone substitute for tissue engineering.